GEOGRAPHY IN THE ORGANIZATIONAL STRUCTURE OF ACADEMIC INSTITUTIONS – SELECTED ISSUES - Jerzy BANSKI (European Journal of Geography)
The goal of this article is to indicate the position that geography occupies within the organization structure of universities in given countries and to provide an overview of the research of research that predominated in the institutions and departments connected to geography in these universities. Separately, I draw attention to the structure of geographical institutions in Poland and identify the most serious institutional and organizational issues that hamper their effectiveness and development. The results seem to point to a process of gradual disintegration of the field. Research teams in the area of physical geography are clearly drifting towards the “hard sciences”, and within them, particularly the natural sciences, while research agendas that deal with socio-economic geography are strongly leaning towards the humanities. The link between physical geography and its related fields of study (geology, ecology, geophysics), however, seems to be the prevalent one, which explains the increasingly interdisciplinary nature of research teams handling modern-day environmental problems. Finally, an overview of institutes of geography has established that these typically fall under departments of natural sciences rather than social sciences or the humanities.